2020
DOI: 10.1038/s41598-020-58438-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of synergistic drug combinations using breast cancer patient-derived xenografts

Abstract: Compared with other breast cancer subtypes, triple-negative breast cancer (TNBC) is associated with relatively poor outcomes due to its metastatic propensity, frequent failure to respond to chemotherapy, and lack of alternative, targeted treatment options, despite decades of major research efforts. Our studies sought to identify promising targeted therapeutic candidates for TNBC through in vitro screening of 1,363 drugs in patient-derived xenograft (PDX) models. Using this approach, we generated a dataset that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 87 publications
2
27
0
Order By: Relevance
“…Its expression and/or activity can be modulated by muscarinic receptors [38]. Several authors consider that the sole up-regulation of EGFR expression is a bad prognosis marker and an indicator of chemoresistance in TNBC patients or cell lines [39][40][41]. Our results demonstrated that the combination of PX plus carbachol or APE drastically reduced EGFR expression in tumor cells and this effect should be beneficial in the treatment of this type of tumor.…”
Section: Plos Onesupporting
confidence: 51%
“…Its expression and/or activity can be modulated by muscarinic receptors [38]. Several authors consider that the sole up-regulation of EGFR expression is a bad prognosis marker and an indicator of chemoresistance in TNBC patients or cell lines [39][40][41]. Our results demonstrated that the combination of PX plus carbachol or APE drastically reduced EGFR expression in tumor cells and this effect should be beneficial in the treatment of this type of tumor.…”
Section: Plos Onesupporting
confidence: 51%
“…For instance, combinatorial CRISPR-based screens may identify effective means with which to target ITH in breast tumor samples [ 151 ]. Large-scale drug screening platforms, such as those enabling high-throughput two-drug combination testing in PDX-derived cells [ 152 ], hold promise to identify combinations that are synergistically cytotoxic across multiple models. Use of cells that can be subsequently xenografted allows for in vivo validation of in vitro drug screen hits, further increasing the probability of clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, direct comparison of tamoxifen response in patients with their matched organoid cultures revealed congruent responses ( 14 ). Similarly, organoids have been derived from orthotopic PDX models, enabling high-throughput drug screening with panels of SOC and experimental compounds, providing novel avenues for preclinical drug testing ( 132 ) and synergistic combinations ( 133 ). Direct genomic and pharmacologic comparisons of organoids in vitro and tumors derived from orthotopic xenotransplantation into mice has revealed a high degree of concordance ( 16 ).…”
Section: In Vitro Models Of Therapy Resistance—2dmentioning
confidence: 99%